Defensive realism and the Concert of Europe - Rendall, Matthew (British International Studies Association, 2006)
Why do great powers expand? Offensive realist John Mearsheimer claims that states wage an eternal struggle for power, and that those strong enough to seek regional hegemony nearly always do. Mearsheimer's evidence, however, displays a selection bias. Examining four crises between 1814 and 1840, I show that the balance of power restrained Russia, Prussia and France. Yet all three also exercised self-restraint; Russia, in particular, passed up chances to bid for hegemony in 1815 and to topple Ottoman Turkey in 1829. Defensive realism gives a better account of the Concert of Europe, because it combines structural realism with non-realist theories of state preferences.